Trust, Perceived Support and Organizational Citizenship Behavior Among Undergraduate Students in Universiti Sains Malaysia - Kee, Daisy Mui Hung; Syazwan, Muhammad Akif; Rusydi, Mohd Danial; Anwar, Mohd Arief; Islah, Mohd Hazim; Khan, Yasmeen Firoz; Ganatra, Varsha (Asia Pacific Journal of Management and Education (APJME), 2021)
Most research on organizational citizenship behavior (OCB) has been conducted in industrial or organizational environments. This paper explores the concept of OCB among undergraduate students in Universiti Sains Malaysia. This paper investigates the link between trust, perceived support, and OCB. The findings indicate that students with high-quality social exchange relationships with their lecturers, classmates, and university are more likely to develop OCB. This indicates that trust and perceived support lead to OCB among undergraduate students. This study provides important insight to university management and academic staff about how trust and perceived support can boost their students’ OCB. The survey was carried out through Google Form. These data were analyzed using SPSS.